Groot. #6 - Loveness, Jeff (Guardians of the galaxy (Series), 2018)
Groot and Rocket finally make it to Earth and go through Groot's checklist of must-do things, but there is one thing above all the rest that he wants to do--find a little girl he rescued long ago.